Does Size Influence Firm Performance? An Impact Assessment on Select Indian Banks (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This study aims to assess the contribution of  the application of financial resources and the  impact of size on firm performance in the Indian  banking industry. A total of nine variables  have been taken for the study, namely, return  on investment, return on advances, return on  fixed assets, number of employees, number of  branches, etc. The study applies panel regression  to analyze the data of 10 public sector banks  and 10 private sector banks for five years from  2016 to 2020. The results confirm the impact of  changes in size on the performance of the banks.  Out of all the nine variables, an increase in  current assets, advances, and employee number  was found to have a positive impact on bank  performance in terms of ROA and ROE whereas  any increase in branch spread and assets apart  from advances, fixed assets, current assets, and  investments is expected to decrease the profit  potential of the firms.
Keywords: Bank size; bank performance; return on assets; return on equity; panel regression